2010
DOI: 10.1002/ijc.25220
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin upregulates insulin‐like growth factor binding protein‐5 (IGFBP‐5) and C/EBPα during oral cancer suppression

Abstract: Curcumin is a common food ingredient derived from the plant Curcuma longa and is a potent drug against tumorigenesis. Both insulin-like growth factor binding protein-5 (IGFBP-5) and CCAAT/enhancer-binding protein a (C/EBPa) are suppressors of head and neck carcinogenesis. We identified curcumin as an inducer of IGFBP-5 expression in multiple types of oral keratinocytes; furthermore, curcumin induces IGFBP-5 promoter activity in SAS oral cancer cells. Promoter deletion mapping identified a region (nt 271 to nt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…It mediates pluripotency by inhibiting various oncogenic signaling pathways including AKT, ß-catenin, Bcl2, ERK, NFκB and others [37], some of which seem to be involved in counteracting EGFR stimulation. Furthermore, curcumin activates p38/MAPK bringing about C/EBPα up-regulation in oral keratinocytes, which results in tumor suppression [31]. In this study, we identified for the first time that EGF is an oncogenic factor that is able to up-regulate miR-31 expression in OSCC cells.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…It mediates pluripotency by inhibiting various oncogenic signaling pathways including AKT, ß-catenin, Bcl2, ERK, NFκB and others [37], some of which seem to be involved in counteracting EGFR stimulation. Furthermore, curcumin activates p38/MAPK bringing about C/EBPα up-regulation in oral keratinocytes, which results in tumor suppression [31]. In this study, we identified for the first time that EGF is an oncogenic factor that is able to up-regulate miR-31 expression in OSCC cells.…”
Section: Introductionmentioning
confidence: 76%
“…These proteins are members of the basic leucine zipper transcription factor group and are important mediators of various physiological and pathological states including tumorigenesis [29]. C/EBPα plays a suppressor role in OSCC and other keratinocytic malignancies by maintaining cellular homeostasis [30], [31]. Various lines of evidence indicate that C/EBPβ is an oncogenic factor.…”
Section: Introductionmentioning
confidence: 99%
“…In SAS oral cancer cells, curcumin induced the promoter activity of insulin-like growth factor binding protein-5 and CCAAT/enhancer-binding protein α, which are involved in the suppression of head and neck cancer. Curcumin exerted an inhibitory effect on these factors through the activation of p38, and resulted in decreased in vivo tumorigenesis in a mouse xenograft model (85). The activity of curcumin has been investigated in a number of head and neck SCC (HNSCC) cell lines, including CAL27, CCL23 (laryngeal), UM-SCC1 and UMSCC14A (oral) (86).…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…Clark et al observed an inhibited tumor growth in mice, via the inhibition of the AKT/MTOR pathway, following treatment with an oral curcumin solution prior to inoculation of SCC40 tongue SCC cells (102). In addition, Chang et al demonstrated the suppression of oral carcinogenesis in mice xenografts (85). Furthermore, Kumar et al (103) developed a novel class of curcumin analogs (H-4073), based on diarylidenylpiperidones (DAP), incorporating a piperidone link to the β-diketone structure and fluoro-substitutions on the phenyl groups.…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…The optimal inhibitor concentrations were determined according to previous studies. 19,20) Statistical Analysis Each experiment was performed at least 3 times. Differences between the control and experimental groups were evaluated by the Mann-Whitney's U-test, the Student's t-test, or the Scheffé's F-test.…”
Section: Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (Smentioning
confidence: 99%